Sustainable antidote: rehabilitating the city of Harare - Muregerera, Rose Tsitsi (My University, 2015)
Abstract With Harare, Zimbabwe, as my reference city, the aim of the study was to explore and substantiate how architecture and landscape can work together to facilitate platforms for the interaction between ‘‘people and nature’’ and ‘‘amongst the people’’. The theoretical themes that helped guide the investigation are phenomenology, place attachment, ecotherapy, healing environments, environmental psychology and sustainability. Over the years Harare has suffered economic downturn which has led to a rapid disintegration of its socio-economic and biophysical systems including physical infrastructure. This has negatively affected the people, creating an atmosphere of disconnection and apathy towards their environment and to each other. The study pursues the objective of a sustainable antidote for the city through development of a healing environment that would rejuvenate, reconnect and inspire the people of Harare to pursue sustainable life styles. Through renewed and reinvigorated relationships, the people can then begin to build one another and in turn develop a positive attitude towards their environment. No matter what the circumstances we are constantly drawn and connected to nature and to each other in a manner similar to what is often captured under the African spirit of Ubuntu. The design intervention developed into a Therapy Performing Arts Centre embedded in the landscape of an open public space in the city. The spaces engage with nature in order to create a sensual experience that seeks to tone down the pace of the people and get them to appreciate their surroundings and one another. The driving concept for the design was reconnecting through moments of pause and motion. The spaces were inspired by the existing paths as guidelines thus allowing the building and nature to be woven together through experiential journeys within the spaces provided. Embedding the building in the landscape allowed for the creation of an intimate connection to nature in order to re-ignite the humannature relationship and thus restoring balance, development and renewal to the health circle. In turn, and over time, this would begin to heal the human-to-human relationships as well.
Keywords: City planning--Zimbabwe--Harare; Community development--Zimbabwe--Harare; Harare (Zimbabwe); Harare (Zimbabwe)--Social conditions